Maximizing Labor Productivity in the Herbal Medicine Industry: The Impact of Training, Motivation, and Work Environment - Febi Dian Mutiasari; Ani Muttaqiyathun; Krishna Kumar (Journal of Management Studies and Development, 2023)
This study aimed to examine the impact of training, motivation, and work environment on the labour productivity of the Jamu Industry Center. The sample consisted of all 85 workers in the herbal medicine industry operation, who were selected using census sampling. A quantitative approach was utilized, and data were collected using questionnaires. Multiple linear regression analysis, partial tests, and simultaneous tests were employed to analyze the data. The results showed that training negatively and significantly affected labour productivity, while motivation and work environment had positive and significant impacts. Furthermore, training, motivation, and work environment collectively influenced labour productivity. The studied variables accounted for 68.3% of the variance in productivity. These findings suggest that improving the work environment and motivation may enhance labour productivity in the herbal medicine industry, while caution should be exercised when implementing training programs.